Discursive Determinants of Youth form Disadvantaged Neighborhoods Empowerment through Participatory Socio-Educational Work. An Example of an Extra-School Education - Anita Gulczyńska; Mariusz Granosik; Anna Jarkiewicz; Małgorzata Kostrzyńska; Magdalena Dubicka; Małgorzata Kucharska (Studia z Teorii Wychowania)
This article presents the results of an analysis that is part of a broader action-research project on the onto-epistemology of Social-Educational Work (SEW) with youth from disadvantaged neighborhoods (DN) in one of Łódź's extra-school educational facilities. We argue that SEW offered in such facilities located within urban underprivileged areas is especially susceptible to the impact of overarching discourses. This vulnerability becomes pronounced when SEW objective is to empower children and youth from these environments. Through the example of a distinctive project that co-creates socio-spatial change with young people from DN – detaching a Youth Club from the conventional structures of a community center in this facility – we have documented how various discourses (economization, psychologization, educationalization) influence the execution of the chosen pedagogical approach in practice. At the background of the human and social strengths identified within the institution and the ways they oppose these processes; in this article we focus more on the critical analysis of discursive conditions.